Bourdieu's habitus and field: implications on the practice and theory of critical action learning. (4th May 2017) - Warwick, Rob; McCray, Janet; Board, Douglas
ABSTRACT: This paper considers the logic of practice of the French sociologist Pierre Bourdieu in relation to critical action learning: in particular habitus which is co-created with field and the interplay amongst the two in the form of misrecognition and risk. We draw on interviews with participants who have experienced action learning as part of an NHS leadership programme. We argue that Bourdieu provides helpful ways of understanding and explaining the complex processes of social interactions which are centre stage in action learning – especially the 'social friction' through which action learners gain new insights and new prompts to action in their workplace from learning set members. These insights can support action learning practitioners keen to explore their own practice.